Synthesis, Structural, Spectroscopic and Electrochemical Properties of Novel S- and S,O-Substituted 1,4-Naphthoquinones - Ibis, Cemil; Sahinler Ayla, Sibel; Gulsah Deniz, Nahide (Asian Journal of Chemistry, 2010)
New S- and S,O-substituted 1,4-naphthoquinone compounds 3, 4 and 5 were synthesized from the reaction of 2,3-dichloro-1,4-naphthoquinone (1) with 2-mercaptobenzylalcohol (2) in ethanol with sodium carbonate for 2 h at room temperature. The structures of novel compounds were characterized by using micro analysis, FT-IR, UV/Vis, 1H NMR, 13C NMR, mass spectra, cyclic voltammetry and fluorescence spectropho-tometer. The crystal structure of 3 was determined by X-ray diffraction method. The compound 3 was crystallized in the triclinic crystal system (space group P-1) with the unit cell parameters a = 7.9433(10) Å, b = 8.1707(11) Å, c =10.5705(11) Å, a = 91.173(6)°, b = 93.564(6)°, g = 106.115(6)°.